Trace-element hydrogeochemistry of thermal waters of Karakocan (Elazig) and Mazgirt (Tunceli), Eastern Anatolia, Turkey - Okan, Ozlem Oztekin; Kalender, Leyla; Cetindag, Bahattin (Elsevier, 2018)
Trace-element hydrogeochemistry is beneficial to define the origin of thermal springs and construct conceptual models of geothermal systems. Hydrogeochemical characteristics of thermal and cold waters in the Karakocan and Mazgirt districts were investigated for trace-element contents in the present study. Thermal and cold waters were collected in dry and rainy seasons to determine whether seasonal variations exist in the chemical composition of the waters. Based on the results, trace-element contents of thermal waters show seasonal changes, except for Co, Cs and Rb. Groundwater-rock and groundwater-clay/alteration mineral interactions are the main processes controlling the thermal and cold water trace-element content. Magmatic-sourced gases ascending through faults and fractures could be another source of B and Cl in thermal and cold waters in the study area. Clays and alteration products of K-minerals are the main sources of Rb and Cs in the thermal waters. High concentrations of As, Sb and Pb in thermal and cold waters are derived from groundwater-rock interaction. As and Sb mobilisation in the thermal waters is predominantly related to the reductive dissolution of Fe-oxyhydroxides and the oxidation of As and Sb containing Mg-Fe sulphur minerals in cold waters. Mixing of deep circulation thermal waters with the shallow cold water aquifers could also be responsible for high As, Sb and Pb concentrations in the cold groundwater.
Keywords: Hydrogeochemistry; Thermal water; Water-rock interaction; Arsenic; Karakocan- Elazig; Mazgirt- Tunceli